Metacognitive Reading Comprehension Instructional Model on Narrative Text: A Mixed Method for Enhancing Students’ Comprehension - Juliana, Juliana; Anggraini, Risa (REiLA : Journal of Research and Innovation in Language, 2024)
This study highlights the integration of metacognitive strategies in reading comprehension through a novel Three-phases instructional model, focusing on metacognitive strategies (pre-reading, while-reading, post-reading). This innovative model is distinct in its holistic approach to enhancing students' reading comprehension by activating their prior knowledge, engaging them actively in the reading process, and fostering reflective comprehension towards a successful strategic reading journey. Targeting narrative texts, the research was conducted with 70 junior school students from Tanjung Morawa, specifically selected for their lower proficiency in reading comprehension, highlighting the model's focus on addressing the needs of struggling readers. Through a mixed-method approach, employing both tests and questionnaires for data collection, the study demonstrated that the instructional model significantly boosts students' reading comprehension. The mean score improvement from 62.85 (pre-test) to 83.71 (post-test) underscores the model's effectiveness and its potential to significantly enhance students' reading comprehension skills. A survey of 35 students further validated the model's role in elevating their awareness and motivation for reading, with making a prediction which got 28 (80.0%) is the most commonly used, followed by restating ideas with 23 (65.7%) and thinking aloud with 21 (60.0%). These results not only bridge the existing gap in reading instruction but also carry significant implications for educational practices and literacy development. It serves as a testament to the potential of innovative instructional models in enhancing reading comprehension.